Functional Outcome of Bicondylar Tibial Fractures Schatzker Type V and VI Treated with Ilizarov External Fixator - Usman, Ahmad; Zia, Muhammad Haseeb (Medical Journal of South Punjab, 2025)
Objective: To determine the mean functional outcome of Schatzker type V and VI bicondylar tibial plateau fractures treated with Ilizarov external fixation. Methodology: Prospective descriptive study conducted at department of Orthopedic Surgery, Nishtar Hospital Multan, from February 20, 2024 to August 20, 2024. Fifty-nine patients with closed Schatzker type V or VI tibial plateau fractures treated with Ilizarov external fixation within 14 days of injury were included. Fractures were reduced via closed or mini-open techniques under fluoroscopic guidance, and fixed with a three or four ring external fixator. Postoperatively, patients underwent supervised physiotherapy. Functional outcomes were assessed using the Karlström-Olerud (KO) score at the final follow-up. Data was analyzed using IBM SPSS, and an independent samples T-test was used to compare mean functional outcome scores. Results: The mean age of the 59 patients, of whom 79.7% were male, was 37.3 ± 14.1 years. The mean KO score was 28.33 ± 3.2, with 11.9% achieving excellent, 39.0% good, 25.4% satisfactory, 15.3% moderate, and 8.5% poor results. Schatzker type VI fractures had significantly lower KO scores than type V fractures (p<0.001). A significant negative correlation was found between the duration from injury to surgery and the KO score (p=0.01). Conclusion: While Ilizarov external fixation can be an effective tool for managing complex bicondylar tibial plateau fractures, the functional outcomes are variable. The complexity of tibial plateau fractures requires a tailored management plan for each patient. Keywords: Bicondylar Fracture, External Fixation, Ilizarov, Karlström-Olerud Score, Tibial Plateau